Perancangan Tempat Sampah Pintar (Smart Trash Bin) Berbasis Arduino di Lingkungan Perumahan - Febrian Amarudin; Bayu Ari Murti; Januar Aksa; Samso Supriyatna (CV. Shofanah Media Berkah, 2025)
Waste management continues to be a major issue in community environments, particularly in residential areas and public spaces. Limited trash bin capacity, low public discipline in disposing of waste properly, and inefficient conventional management systems often lead to waste accumulation and environmental degradation. Therefore, the application of technology is needed to improve cleanliness and efficiency in waste handling. This research aims to design and develop an Arduino Uno-based Smart Trash Bin that operates automatically without requiring direct physical interaction from users. The system employs an HC-SR04 ultrasonic sensor to detect object presence and an SG90 servo motor to control the opening and closing mechanism of the trash bin lid. The research methodology follows the System Development Life Cycle (SDLC) framework, which includes requirement analysis, system design, implementation, and testing stages. The testing results indicate that the system is capable of accurately detecting objects and automatically controlling the lid mechanism based on the predefined distance. Therefore, the proposed Smart Trash Bin is expected to contribute to improved environmental cleanliness, more efficient waste management, and the adoption of smart technology within community settings.